Signal-mediated localization of Candida albicans pheromone response pathway components. Issue 3 (14th December 2020) - Costa, Anna Carolina Borges Pereira; Omran, Raha Parvizi; Law, Chris; Dumeaux, Vanessa; Whiteway, Malcolm
Summary: : A MAPK cascade consists of three kinases, (MEKK, MEK and MAPK), that are sequentially activated in response to a stimulus and serve to transmit signals. In C. albicans and in yeast, an MAPK cascade is linked to the pheromone pathway through a scaffold protein (Cst5 and Ste5, respectively). Cst5 is much shorter and lacks key domains compared to Ste5, so in C. albicans, other elements, in particular the MEKK Ste11, play key roles in controlling the associations and localizations of network components. Abstract: Candida albicans opaque cells release pheromones to stimulate cells of opposite mating type to activate their pheromone response pathway. Although this fungal pathogen shares orthologous proteins involved in the process with Saccharomyces cerevisiae, the pathway in each organism has unique characteristics. We have used GFP-tagged fusion proteins to investigate the localization of the scaffold protein Cst5, as well as the MAP kinases Cek1 and Cek2, during pheromone response in C. albicans . In wild-type cells, pheromone treatment directed Cst5-GFP to surface puncta concentrated at the tips of mating projections. These puncta failed to form in cells defective in either the Gα or β subunits. However, they still formed in response to pheromone in cells missing Ste11, but with the puncta distributed around the cell periphery in the absence of mating projections. These puncta were absent from hst7Δ/Δ cells, but could be detected in the ste11Δ/Δ hst7Δ/Δ double mutant. Cek2-GFP showed a strong nuclear localization late in the response, consistent with a role in adaptation, while Cek1-GFP showed a weaker, but early increase in nuclear localization after pheromone treatment. Activation loop phosphorylation of both Cek1 and Cek2 required the presence of Ste11. In contrast to Cek2-GFP, which showed no localization signal in ste11Δ/Δ cells, Cek1-GFP showed enhanced nuclear localization that was pheromone independent in the ste11Δ/Δ mutant. The results are consistent with CaSte11 facilitating Hst7-mediated MAP kinase phosphorylation and also playing a potentially critical role in both MAP kinase and Cst5 scaffold localization.